A Very Rare Complication of Ethanol Consumption: Non-Traumatic Unilateral Raccoon Eye - Emami, Elham; Dorooshi, Gholamali; Nouri, Keyvan; Samsamshariat , Shiva (Journal of Pediatric Nephrology, 2022)
Ethanol is a chemical that is easily absorbed in all parts of the gastrointestinal tract. This feature increases the risk of poisoning by ingesting this chemical at any amount; the signs and symptoms depend on the poisoned individual. Common symptoms of ethanol poisoning include sedation, poor coordination, vomiting, slurred speech, ataxia, respiratory depression, coma, and death. A rare manifestation of alcohol consumption is the raccoon eye. This article presents a 5-year-old girl who gradually showed a unilateral raccoon eye following ethanol consumption.